2004
DOI: 10.1074/jbc.m402468200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Machinery Is Required in Saccharomyces cerevisiae for the Endoplasmic Reticulum-associated Degradation of a Multispanning Membrane Protein and a Soluble Luminal Protein

Abstract: The folding and assembly of proteins in the endoplasmic reticulum (ER) lumen and membrane are monitored by ER quality control. Misfolded or unassembled proteins are retained in the ER and, if they cannot fold or assemble correctly, ultimately undergo ER-associated degradation (ERAD) mediated by the ubiquitin-proteasome system. Whereas luminal and integral membrane ERAD substrates both require the proteasome for their degradation, the ER quality control machinery for these two classes of proteins likely differs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
295
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(317 citation statements)
references
References 74 publications
(107 reference statements)
12
295
2
1
Order By: Relevance
“…Recently, it was reported that a membrane protein and a soluble luminal protein in the ER were degraded by distinct cellular mechanisms (Taxis et al, 2003;Huyer et al, 2004;Vashist and Ng, 2004). In addition, two ER surveillance mechanisms have been proposed: ERAD-L, which monitors the folded state of luminal domains; and ERAD-C, which monitors that of cytosolic domains (Ahner and Brodsky, 2004;Vashist and Ng, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that a membrane protein and a soluble luminal protein in the ER were degraded by distinct cellular mechanisms (Taxis et al, 2003;Huyer et al, 2004;Vashist and Ng, 2004). In addition, two ER surveillance mechanisms have been proposed: ERAD-L, which monitors the folded state of luminal domains; and ERAD-C, which monitors that of cytosolic domains (Ahner and Brodsky, 2004;Vashist and Ng, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We further examined the role of ubiquitin ligases (E3) in the degradation of Gas1*p. We selected three kinds of E3 that are thought to be involved in ERAD pathway, including the gene products of HRD1, which is involved in ERADlumenal (ERAD-L) pathway (Ahner and Brodsky, 2004;Huyer et al, 2004;Vashist and Ng, 2004); DOA10, which is involved in ERAD-cytosolic (ERAD-C) pathway; and RSP5, which is assumed to be involved in ERAD of misfolded protein when overproduced (Haynes et al, 2002). Unexpectedly, the degradation of HA-Gas1*p was not stabilized in hrd1⌬ and doa10⌬ cells ( Figure 5A).…”
Section: Construction and Characterization Of Misfolded Gas1mentioning
confidence: 99%
“…Not only is this process energetically expensive but also it challenges the cell to prevent these proteins from forming insoluble aggregates when the hydrophobic TMs are exposed to the hydrophilic environment of the cytosol. Indeed, specific AAA-ATPases, such as p97, and other molecular chaperones provide the driving force for dislocation and prevention of protein aggregation (Nishikawa et al, 2001;Ye et al, 2001;Elkabetz et al, 2004;Huyer et al, 2004;Bar-Nun, 2005;Buck et al, 2007;Lipson et al, 2008). The current study describes a system that should allow dissecting the steps in dislocation of polytopic ERAD substrates en route to proteasomal degradation and identification of cellular components that take part in this process.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane protein CFTR has relatively large cytosolic domains that are monitored by at least two checkpoints located on the cytosolic side of the ER membrane (Younger et al, 2006). Lumenal proteins and membrane proteins with relatively large lumenal domains are monitored by quality-control machinery located in the ER lumen (Huyer et al, 2004;Vashist and Ng, 2004). The glycosylation status of these proteins provides cues as to the progression of folding This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E07-07-0674) on April 9, 2008.…”
Section: Introductionmentioning
confidence: 99%